Applying the heat conduction-based 3D normalization and thermal tomography to pulsed infrared thermography for defect characterization in composite materials; International Journal of Heat and Mass Transfer; Vol. 94 - Pawar S. S. Sachin Sampatrao (2016, 2016)
Title screen